Analysis of Determinants of Export Performance of Indonesian Fashion SMEs from the Perspectives of the Resource-Based View and Internationalisation Theory - Rita Anggraini Rahayu; Sudarmiatin Sudarmiatin; Heri Pratikto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Indonesian fashion SMEs have significant export opportunities, but their export performance remains suboptimal as not all businesses are able to convert innovation, digitalisation, and market orientation into tangible international competitiveness. This study aims to analyse the determinants of Indonesian fashion SMEs’ export performance from the perspectives of the Resource-Based View and Internationalisation Theory. The study employs an explanatory quantitative approach using a cross-sectional survey design involving 200 owners or key managers of fashion SMEs in East Java, selected through purposive sampling. Data were analysed using SEM-PLS. Simulation results indicate that internal capabilities, international market orientation, and access to international networks have a positive influence on competitive advantage, whilst competitive advantage has a positive influence on export performance. Internal capabilities and access to international networks also demonstrate a significant direct influence on export performance, whilst international market orientation is not directly significant but operates through competitive advantage. The implication is that strategies to boost fashion SME exports should focus on strengthening innovation, quality, brand differentiation, and international market networks, rather than merely on symbolic digital adoption.